US Counterproliferation Policy in the Late XX – Early XXI century - K. S. Tarasov (Vestnik MGIMO-Universiteta)
This article, which covers the period till September 2012, presents a comprehensive review of the US counterproliferation strategy, its genesis, implementation and consequences. The author also outlines Russia’s nonproliferation initiatives and unveils possible steps to strengthen nonproliferation regime.